以素養導向觀點探討中等學校藝術師資培育教材教法課程現況與實踐Discussion From a Competence-Oriented Perspective on the Status Quo and Practice of the Secondary School Teacher Training "Arts Teaching Material and Methods" Curriculum - 陳育祥 Yu-Hsiang Chen (National Taiwan Normal University, 2018)
鑑於十二年國民基本教育課程綱要總綱核心素養理念，藝術領域課程綱要核心素養與學習重點也依循對應與發展，藝術師資培育階段面對十二年國民基本教育課程政策的典範轉移與實踐轉化，亦需以現存之情境脈絡、處境與課題進行思考。本研究除以文獻梳理探討中等教育階段藝術領域師資培育的學術發展趨勢，並蒐集藝術師資培育單位分科／領域教材教法課程大綱，透過課程大綱文件內容分析與教材教法授課教師個別訪談，將資料概念化與類目化交叉比對，以探討師資培育階段藝術分科／領域教材教法課程與實踐現況。研究結果指出，受到藝術師資生起點行為、課程時數與教師甄選實際考量因素，藝術教材教法課程之現況重視教案設計與教學能力、學習內容多元變異性高、課程綱要之理解與鑑賞教學內容缺乏、合科教學成效不佳等情形，面對未來十二年國民基本教育課程綱要施行，有待思考素養導向之實踐，本研究依據結果提出相關建議。 Because the curriculum guidelines of 12-year compulsory education consider competency to be its core philosophy, the guidelines drafted for the arts curriculum thus include key learning points and the development of core competencies. However, in addition to these guidelines, changes to the practice and requirements of arts teacher training programs in accordance with this shift in policy require investigation. Through a literature review, this study offers a discussion of the trend of academic development in secondary school teacher training programs. In addition to collecting syllabi for "fine arts/visual arts teaching materials and methods" from teacher training institutes, the researcher conducted individual interviews with instructors of these courses. Through interviews and an analysis of document contents, the data were conceptualized and categorized to cross-verify and investigate the status quo and practice of the "teaching materials and methods" curriculum in teacher training programs. The research results indicated discrepancies in preservice teacher entry behavior, number of teaching hours, and anxiety related to participating in screening tests, and that these factors had the most significant effect on teaching competence and lesson plan design. Significant variance was observed among teacher responses to learning contents, including inadequate understanding of curriculum guidelines, insufficient appreciation for teaching arts, and ineffective interdisciplinary teaching. Therefore, how arts teaching materials and methods are practiced during the implementation of 12-year compulsory education curriculum guidelines requires further investigation. Suggestions are also provided in this study based on the research results.